Incidence and Etiology of Mid-facial Fractures: A 10 Year Retrospective Institutional Study - Arvind, Karikal; V., Kotecha Priyank (Journal of Health and Allied Sciences NU, 2016)
The aim of this study is to collect retrospective data regarding the patients reporting with midfacial fractures over the past 10 years and analyze the data, the results of which can be of further assistance in future clinical and research areas. The hospital records of 507 patients treated for maxillofacial trauma from January 2005 to December 2014, were obtained from the medical records department and dental records department and were reviewed and analyzed.Male: Female ratio of 6.5:1 was noted. Dentoalveolar fracture was found to be present in 80 case (15.8%). Nasal bone fracture in 146 cases (28.8%). ZMC fracture in 212 cases (41.8%). Maxillary sinus wall fracture 186 cases (36.7%) Lefort I fracture 29 case (5.7%) Lefort II fracture in 6 case (1.2%) Isolated lefort III fracture in only a single case (0.2%). Fracture involving both ZMC and orbit were noted in 20 cases (3.9%) while 24 cases (4.7%) of orbital floor fracture were noted. RTA & Fall were two most common etiology.The present study supports that regular epidemiologic evaluations of maxillofacial fractures allow a detailed analysis of these lesions, providing support to install clinical and research priorities, since risk factors and patterns of presentation can be identified.
Keywords: Midfacial Fractures; Zygomaticomaxillary; nasal bone